Fabrication and characterization of TGG crystals containing paramagnetic rare-earth ions. (September 2016) - Chen, Zhe; Hang, Yin; Wang, Xiangyong; Hong, Jiaqi
Abstract: Highly transparent Tb3− x Re x Ga5 O12 (RE=Ce, Pr and Nd) single crystals were grown by the Czochralski (Cz) method. The optical and magneto-optical properties of Tb3− x Re x Ga5 O12 were analyzed in detailed. Tb3− x Re x Ga5 O12 exhibited very high transmittance in the visible-near infrared region (VIS–NIR). The absorption coefficient and Faraday rotation spectrum were investigated at VIS–NIR region at room temperature. The remarkable higher Verdet constants (V) and figure of merit showed superior characteristics of Tb3− x Re x Ga5 O12 compared to that of Tb3 Ga5 O12 (TGG). We also investigated the thermal conductivity and laser induced damage threshold (LIDT) of the crystals. The superior performance of the materials indicate that Tb3− x Re x Ga5 O12 have great potential to meet the increasing demand for magneto-optical devices in the VIS–NIR region.